Barriers and facilitators experienced in collaborative prospective research in orthopaedic oncology: A qualitative study. Issue 5 (May 2017) - Rendon, J. S.; Swinton, M.; Bernthal, N.; Boffano, M.; Damron, T.; Evaniew, N.; Ferguson, P.; Galli Serra, M.; Hettwer, W.; McKay, P.; Miller, B.; Nystrom, L.; et al.
Abstract : Objectives: As tumours of bone and soft tissue are rare, multicentre prospective collaboration is essential for meaningful research and evidence-based advances in patient care. The aim of this study was to identify barriers and facilitators encountered in large-scale collaborative research by orthopaedic oncological surgeons involved or interested in prospective multicentre collaboration. Methods: All surgeons who were involved, or had expressed an interest, in the ongoing Prophylactic Antibiotic Regimens in Tumour Surgery (PARITY) trial were invited to participate in a focus group to discuss their experiences with collaborative research in this area. The discussion was digitally recorded, transcribed and anonymised. The transcript was analysed qualitatively, using an analytic approach which aims to organise the data in the language of the participants with little theoretical interpretation. Results: The 13 surgeons who participated in the discussion represented orthopaedic oncology practices from seven countries (Argentina, Brazil, Italy, Spain, Denmark, United States and Canada). Four categories and associated themes emerged from the discussion: the need for collaboration in the field of orthopaedic oncology due to the rarity of the tumours and the need for high level evidence to guide treatment; motivational factors for participating in collaborative research including establishing proof of principle, learning opportunity, answering a relevant research question and being part of a collaborative research community; barriers to participation including funding, personal barriers, institutional barriers, trial barriers, and administrative barriers and facilitators for participation including institutional facilitators, leadership, authorship, trial set-up, and the support of centralised study coordination. Conclusions: Orthopaedic surgeons involved in an ongoing international randomised controlled trial (RCT) were motivated by many factors to participate. There were a number of barriers to and facilitators for their participation. There was a collective sense of fatigue experienced in overcoming these barriers, which was mirrored by a strong collective sense of the importance of, and need for, collaborative research in this field. The experiences were described as essential educational first steps to advance collaborative studies in this area. Knowledge gained from this study will inform the development of future large-scale collaborative research projects in orthopaedic oncology. Cite this article: J. S. Rendon, M. Swinton, N. Bernthal, M. Boffano, T. Damron, N. Evaniew, P. Ferguson, M. Galli Serra, W. Hettwer, P. McKay, B. Miller, L. Nystrom, W. Parizzia, P. Schneider, A. Spiguel, R. Vélez, K. Weiss, J. P. Zumárraga, M. Ghert. Barriers and facilitators experienced in collaborative prospective research in orthopaedic oncology: A qualitative study. Bone Joint Res 2017;6:–314. DOI: 10.1302/2046-3758.65.BJR-2016-0192.R1.